Association between R.E.N.A.L nephrometry score and perioperative outcomes following open partial nephrectomy under cold ischemia - Park, Dong Soo; Hwang, Jin Ho; Kang, Moon Hyung; Oh, Jong Jin (Canadian Urological Association Journal, 2014)
Introduction: We investigate the clinical significance of the R.E.N.A.L. nephrometry score for renal neoplasm following open partial nephrectomy (PN) under cold ischemia. Methods: A retrospective analysis was conducted using clinical data of 98 consecutive patients with clear cell renal cell carcinoma who underwent open PN by a single surgeon from December 2000 to September 2012. Tumour complexity was stratified into 3 categories: low (4-6), moderate (7-9) and high (10-12) complexity. Perioperative outcomes, such as complications, cold ischemic time, estimated blood loss and renal function, were analyzed according to the complexity by NS. Complications were stratified using the Clavien-Dindo classification system. Results: Tumour complexity according to nephrometry score was assessed as low in 16 (16.3%), moderate in 48 (49.0%) and high in 34 (34.7%). The median cold ischemic time did not differ significantly among the 3 groups (36.0 minutes in low-, 40 minutes in moderate- and 43 minutes in the high-complexity group, p = 0.421). Total complications did not differ significantly (2 (2.0%) in low, 4 (4.1%) in moderate and 4 (4.1%) in high, p = 0.984). Each Grade 3 complication occurred in the moderate (urine leakage) and high groups (lymphocele). Postoperative renal functional outcomes were similar among the groups (p = 0.729). Only mean estimated blood loss was significantly different with nephrometry score (p = 0.049). Conclusions: The nephrometry score, as used in an open PN series under cold ischemia, was not significantly associated with perioperative outcomes (i.e., ischemia time, complications, renal functional preservation).